2017
DOI: 10.4172/2155-9597.1000308
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Cryptosporidium Infection in Children Hospitalized for Diarrhea in Guangzhou, China

Abstract: This study was conducted to determine the prevalence, species and risk factors of Cryptosporidium infection in children hospitalized for diarrhea in Guangzhou region of China. A cross-sectional study was conducted to assess the prevalence and risk factors of Cryptosporidium infection in children (2 weeks to 10 years old) who were hospitalized for diarrhea. Cryptosporidium oocysts were detected using direct immunfluorescent assay and species were determined by sequencing a fragment (~800 bp) of the 18S rRNA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…No significant differences in the occurrence of the two protozoal parasites were found between pools in urban and suburban areas. This is converse to our previous findings that prevalence of Cryptosporidium was significantly higher in children hospitalized in suburban hospitals than in urban hospitals in the same area [ 17 ]. This is probably because of the different transmission routes of Cryptosporidium in children patients living in urban and suburban areas.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No significant differences in the occurrence of the two protozoal parasites were found between pools in urban and suburban areas. This is converse to our previous findings that prevalence of Cryptosporidium was significantly higher in children hospitalized in suburban hospitals than in urban hospitals in the same area [ 17 ]. This is probably because of the different transmission routes of Cryptosporidium in children patients living in urban and suburban areas.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to limited numbers of (oo) cysts detected from pool water we did not characterize the two parasites by genotyping, hence the genotypes and zoonotic potential of the two parasites in pool water were unknown. In our previous study we found that the dominant species of Cryptosporidium in children hospitalized for diarrhea in the same area was C. parvum , a species that infects humans and a wide range of animals [ 17 ]. Also, because of the limited numbers of oocysts detected in samples, we did not assess the viability of oocysts, therefore, it was unknown if the oocysts detected in pool water were infective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in human cryptosporidiosis have reported similar isolation rates. For example, Chen, et al 43 , found C. parvum infection in 6.9% of tested children in China. Additionally, several studies have found that immunocompromised individuals have high prevalence of cryptosporidiosis than healthy individuals 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%